PENGARUH PENGGUNAAN MEDIA PAPAN PINTAR UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI KPK DAN FPB KELAS IVA MIN 1 LAMONGAN - Ainun, Muhammad (Journal Of Islamic Elementary School (JIES), 2019)
This study aims to determine the effectiveness of the use of KPK and FPB smart board media in learning Mathematics to determine the value of Least Common Multiple (KPK) and Largest Common Factor (FPB) in improving student learning outcomes. This study uses classroom action research (CAR) which is carried out in two cycles and each cycle includes the stages of planning (planning), implementing action (action), observation (observation) and reflection (reflection) with data collection techniques using observations, tests and documentation. The results showed that student learning outcomes in pre-action the average value of students was 50 and the percentage of students' completeness reached 40%, in the first cycle the average value of students was 82 and the percentage of students' completeness reached 76%, and in the second cycle there was an increase in the score. an average of 92 and the percentage of students' completeness reached 96%. This shows that the use of the KPK and FPB smart board media is more effective in instilling the mathematical concepts of Least Common Multiple (KPK) and Largest Common Factor (FPB) students of class IVA MIN 1 Lamongan in the odd semester of the 2019/2020 school year.